2007
DOI: 10.1016/j.bej.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Co-composting of sewage sludge:fats mixtures and characteristics of the lipases involved

Abstract: Co-composting of sewage sludge and animal fat mixtures was studied in order to determine the possibility of using this technology to recycle fat-enriched wastes. A maximum fat content of 30% in fat:sludge mixtures is recommended to achieve the international sanitation requirements on compost quality and to avoid an excessive thermophilic composting time. Under these conditions a fat content reduction of 85% was achieved. Biological activity was highly dependent on the moisture content as shown by the respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
4
33
0
5
Order By: Relevance
“…Gea et al [25] observed that fat degradation has an important role in the preservation of high temperatures in the reactor with higher fat contents resulting in longer processes. However, in this case a more stable product was obtained in a shorter time from an initial material with higher fat content indicating thus that the control strategy used effectively improved the process despite the higher fat content.…”
Section: Experiments 2: Temperature and Oxygen Controlmentioning
confidence: 99%
“…Gea et al [25] observed that fat degradation has an important role in the preservation of high temperatures in the reactor with higher fat contents resulting in longer processes. However, in this case a more stable product was obtained in a shorter time from an initial material with higher fat content indicating thus that the control strategy used effectively improved the process despite the higher fat content.…”
Section: Experiments 2: Temperature and Oxygen Controlmentioning
confidence: 99%
“…They focused in particular to phosphatase and dehydrogenase activity [121]. Focusing more on the fats mixtures and the effect of lipase on co-composting sludges, Gea et al [122] reported 85% reduction in fat content, with an initial fat content of 30%. The authors note that due to hydrophobic nature of the fats, the moisture content needs to be maintained above 40%.…”
Section: The Use Of Enzymes For Plant Nutritionmentioning
confidence: 99%
“…The preparations with lipasic activity can be used for the treatment of oil waste [8][9]. By using immobilized lipa sic preparations it's possible not only to degrade oil waste, but also to recycle it into biofuel [10,11], biooil and other compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%